Online Identity Analysis of Dokter Detektif As a Skincare Product Education Doctor On Tiktok Social Media: Analisis Identitas Online Dokter Detektif Sebagai Dokter Edukasi Produk Perawatan Kulit Di Media Sosial Tiktok - Tiara, Mutiara Mujahidah Hanifah (Universitas Muhammadiyah Sidoarjo, 2025)
Detective Doctor or commonly known as Doktif, a Beauty Doctor is also a public figure who is active on social media, especially on the Tiktok platform. The Doktif TikTok account that is usually used to actively produce content is @DokterDetektif. The detective doctor is known as an educator who focuses on skincare products. By using a Mask on his eyes which is typical of a Detective Doctor. He is known to be critical of excessive claims that are often found in beauty products, especially related to active ingredients that do not match This study seeks to assess and interpret the laboratory test results created by the Detective Doctor. his online identity as an educator of beauty / skincare products on social media, especially Tiktok, by using a Mask for his disguise. This study applies Erving Goffman's Dramaturgy theory and employs a qualitative descriptive research method through observations conducted on TikTok social media. The findings of the study are derived from the analysis. show that the Detective Doctor has succeeded in providing education based on official evidence even though the identity of the Detective Doctor is kept secret.